If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 135 Reorder the terms: 3 + 6x = 135 Solving 3 + 6x = 135 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = 135 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 135 + -3 6x = 135 + -3 Combine like terms: 135 + -3 = 132 6x = 132 Divide each side by '6'. x = 22 Simplifying x = 22
| 90-2x=25x+15 | | 12-14x=0 | | 3x/5=9/4 | | 25/40=5/x | | n/12=6/18 | | 4+12x=104+x | | 2x+4=y/3 | | (169.25*70.14)-15922= | | 2d+3c=15 | | x^2-2x=x | | 4-(-h)=12 | | 50=80-x | | x^2-4=2x-1 | | 4x+5=x+17 | | -7x+23=37 | | 89+34x=466 | | 2g-12=b | | 2*g-12=x | | 202-6X=7X+23 | | 2(4x)(3y)-4x(7y)= | | x/2+3=-6 | | 3x+3y+5z=113 | | 4+2=2y+6 | | 8/7=6/4x+3 | | x/16=8/32 | | 3x(3y)= | | -69-2x=-11-10x | | 5a+7=-12 | | (2x+3y)(3x-2y)=0 | | (2x+3y)(3x-2y)=-x-8y+2 | | x-4/2=-5 | | 12-5(2w-13)=3(2x-5) |